THEORETICAL EXPLORATION OF THE CAFE'S PROXEMICS AS A TRANSITIONAL EDUCATIONAL SPACE - Sakuntala Verlista; Djuli Djatiprambudi; I Nyoman Lodra (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This paper was a theoretical exploration of proxemic discourse and the experience of cafe space as a transitional educational space. It was based on the development of a paradigm in the 21st century that has targeted the cafe sector and provided the potential to be converted into an alternative educational space, especially for the millennial generation, called students. This study theoretically explored based on the phenomena seen at Yoman Cafe in Surabaya, Indonesia, which often became an alternative learning place for students at Universitas Negeri Surabaya. The research was conducted through participatory observations during March 2021, and it was analyzed by carrying out theoretical exploration of proxemics, spatial experiences, and alternative spaces. The results showed that the cafe currently had a dual role which was known as hybrid. Apart from being a cafe with the traditional definition of being a place to eat, the current cafe also had a role as an alternative space. This was based on the achievement of several aspects to create a sense of comfort as a transitional educational space, namely table settings that provided private space for visitors, comfortable and comprehensive furniture, selection of materials, ambiance entertainment, lighting and acoustics, colors, and use of aesthetic elements.